Risk Profile for Preventable Hospitalizations in Older Adults: Challenges for the Interoperability of Health Networks; [Perfil de Riesgo Para Hospitalizaciones Evitables en Personas Mayores: Desafíos Para la Interoperabilidad de Las Redes de Salud] - Espinosa-Ferrada, V (Sociedad Medica de Santiago, 2024)
Health research teams routinely face difficulties processing clinical data to determine risk profiles in susceptible populations. Aim: Generate a risk profile of avoidable hospitalizations in older adult patients using integrated healthcare networks of the Southern Metropolitan Health Service (SSMS) of the Metropolitan Region of Chile from 2019-2021. Methods: The present research has a retrospective longitudinal descriptive design of anonymized clinical database records from four Family Health Centers and a high-complexity South Metropolitan Health Service (SMHS) hospital. The information available in TRACKCARE and RAYEN records for 2019-2021 was cleaned and filtered, considering only the ICD-10 diagnoses of interest. Demographic and clinical data analysis was performed with descriptive and inferential statistics using GraphPad Prism v5.0. Results: 57.2% of older adults are women with an average age of 74.2 ± 7.2 (P= 0.0352). There is a different distribution profile of the FONASA section between men and women (P= 0.0002) even when 74% of the total sample is affiliated with FONASA-B. 62.7% have a single ICD-10 diagnosis, the majority being high blood pressure and heart failure (I10-I11), reaching 34% of diagnoses. Conclusions: Despite the evident lack of interoperability between the available clinical registry bases, it was possible to identify a sociodemographic and clinical profile of people aged 65 years and more prone to avoidable hospitalizations. This is through a process of collection and cleansing from different sources of information available in the South Metropolitan Health Service and involved communities. © 2024 Sociedad Medica de Santiago. All rights reserved.
Keywords: Chile; Health Services Accessibility; Health Services; Primary Health Care